Determination and correlation of solubility and solution thermodynamics of oxiracetam in three (alcohol + water) binary solvents. (May 2016) - Li, Kangli; Du, Shichao; Wu, Songgu; Cai, Dongchen; Wang, Jinxu; Zhang, Dejiang; Zhao, Kaifei; Yang, Peng; Yu, Bo; Guo, Baisong; Li, Daixi; Gong, Junbo
Graphical abstract: Highlights: The solubility of racemic oxiracetam in three binary solvents were determined. The experimental solubility of racemic oxiracetam were correlated by four models. The dissolution thermodynamic properties of racemic oxiracetam were calculated. Abstract: In this paper, we proposed a static analysis method to experimentally determine the (solid + liquid) equilibrium of racemic oxiracetam in (methanol + water), (ethanol + water) and (isopropanol + water) binary solvents with alcohol mole fraction ranging from 0.30 to 0.90 at atmosphere pressure ( p  = 0.1 MPa). For the experiments, the temperatures range from (283.15 to 308.15) K. The results showed that the solubility of oxiracetam increased with the increasing temperature, while decreased with the increasing organic solvent fraction in all three tested binary solvent systems. The modified Apelblat model, the CNIBS/Redlich–Kister model, the combined version of Jouyban–Acree model and the NRTL model were employed to correlate the measured solubility values, respectively. Additionally, some of the thermodynamic properties which can help to evaluate its dissolution behavior were obtained based on the NRTL model.